2014
DOI: 10.1186/1471-2474-15-248
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the association of patient expectations with changes in health-related quality of life outcomes, following total joint replacement

Abstract: BackgroundPatient expectations regarding surgery may be related to outcomes in total joint replacement (TJR). The aim of this study was to determine the association of patient expectations with health related quality of life (HRQoL) outcomes measured by Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Short Form 12 (SF-12) and satisfaction with current symptoms measured on a 4-point Likert scale, one year after surgery, adjusting for Body Mass Index (BMI), age, gender, joint, educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 51 publications
(74 reference statements)
2
44
1
2
Order By: Relevance
“…We lost 8% of the study cohort to follow-up for unknown reasons. Compared to other prospective cohort studies, the drop-out rate in our case was rather low [20]. Still, we cannot exclude the risk of attrition bias due to a selective drop-out of nonresponders which would lead to a slight overestimation of outcome evaluations and global effectiveness ratings.…”
Section: Limitationsmentioning
confidence: 56%
See 1 more Smart Citation
“…We lost 8% of the study cohort to follow-up for unknown reasons. Compared to other prospective cohort studies, the drop-out rate in our case was rather low [20]. Still, we cannot exclude the risk of attrition bias due to a selective drop-out of nonresponders which would lead to a slight overestimation of outcome evaluations and global effectiveness ratings.…”
Section: Limitationsmentioning
confidence: 56%
“…The willingness to return to an institution for postoperative monitoring or other surgical procedures strongly depends on the patients' evaluation of treatment effectiveness and their satisfaction with postoperative outcomes [19,20]. Important technical progress has already been made in the area of THA which reduces the chances of future major breakthroughs in this eld [21].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that there is an association between patient expectations and outcomes after TJA. 11,12 The expectation of complete pain relief and the expectation of a low risk of complications were independent predictors postoperatively of better physical function, pain improvement, and patient satisfaction following TJA. 11 Ultimately, they determine that patient expectations are independent predictors of improved functional outcomes and satisfaction postoperatively after TJA.…”
Section: Discussionmentioning
confidence: 96%
“…Gonzalez Saenz de Tejada et al evaluated the association between patient expectations with health-related quality of life outcomes (HRQoL) as measured by The Western Ontario and McMaster Universities Osteoarthritis Index and Short-Form 12 and satisfaction with current symptoms. 12 It was determined that patients with higher expectations were more likely to be satisfied postoperatively and had greater improvements in HRQoL. Knowing this information, we can play a pivotal role as surgeons by emphasizing the positive outcomes from TJA.…”
Section: Discussionmentioning
confidence: 99%
“…Испанские исследователи проанализировали у 892 пациентов взаимосвязи ожиданий от операции по замене сустава и качество жизни через год после операции. Полученные результаты показали, что у пациентов, имеющих более высокие начальные ожидания относительно операции, выявлена большая вероятность улучшения качества жизни и двигательной активности по сравнению с пациентами, имеющими изначально более низкие ожидания от оперативного вмешательства [8].…”
unclassified